Triclosan Impairs Hippocampal Synaptic Plasticity and Spatial Memory in Male Rats - Arias-Cavieres, Alejandra; More, Jamileth; Vicente, José Miguel; Adasme, Tatiana; Hidalgo, Jorge; Valdés, José Luis; Humeres, Alexis; Valdés-Undurraga, Ismael; Sánchez, Gina; Hidalgo, Cecilia; Barrientos, Genaro (Frontiers in Molecular Neuroscience, 2018)
Triclosan, a widely used industrial and household agent, is present as an antiseptic ingredient in numerous products of everyday use, such as toothpaste, cosmetics, kitchenware, and toys. Previous studies have shown that human brain and animal tissues contain triclosan, which has been found also as a contaminant of water and soil. Triclosan disrupts heart and skeletal muscle Ca2+ signaling, damages liver function, alters gut microbiota, causes colonic inflammation, and promotes apoptosis in cultured neocortical neurons and neural stem cells. Information, however, on the possible effects of triclosan on the function of the hippocampus, a key brain region for spatial learning and memory, is lacking. Here, we report that triclosan addition at low concentrations to hippocampal slices from male rats inhibited long-term potentiation but did not affect basal synaptic transmission or paired-pulse facilitation and modified the content or phosphorylation levels of synaptic plasticity-related proteins. Additionally, incubation of primary hippocampal cultures with triclosan prevented both the dendritic spine remodeling induced by brain-derived neurotrophic factor and the emergence of spontaneous oscillatory Ca2+ signals. Furthermore, intra-hippocampal injection of triclosan significantly disrupted rat navigation in the Oasis maze spatial memory task, an indication that triclosan impairs hippocampus-dependent spatial memory performance. Based on these combined results, we conclude that triclosan exerts highly damaging effects on hippocampal neuronal function in vitro and impairs spatial memory processes in vivo.